Is government really solving the housing problem? - Monsod, Toby C. ([Quezon City] School of Economics, University of the Philippines, 2011)
Informal housing arrangements, substandard structures, congestion, and land-use conflicts characterize the urban housing problem in the Philippines. The record suggests that response of the state, especially its reliance on below-market-priced mortgage loans, has aggravated the situation.
Title was 'Philippine Review of Business and Economics' until 1979. Title changed to 'Philippine Review of Economics and Business' from 1980-2000, and again changed to 'Philippine Review of Economics' since 2001.
Includes bibliographical references (pages 143-145).
Keywords: Housing -- Philippines; Housing policy -- Philippines